Water Treatment Effect, Microbial Community Structure, and Metabolic Characteristics in a Field-Scale Aquaculture Wastewater Treatment System - Li, Zhifei; Yu, Ermeng; Zhang, Kai; Gong, Wangbao; Xia, Yun; Tian, Jingjing; Wang, Guangjun; Xie, Jun (Frontiers in Microbiology, 2020)
Avoiding and mitigating the introduction of harmful effluent into the environment must be a key part of intensive industrial aquaculture development in order to minimize pollution impacts. We constructed a novel field-scale aquaculture wastewater treatment system (FAWTS) involving three-stage purification to efficiently remove nutrients from effluent wastewater. However, the mechanisms of nutrient attenuation in the FAWTS are still unclear. Since microbiota play an important role in the treatment of aquatic pollutants, we hypothesized that the different stages of FAWTS may have enriched various nutrient-metabolizing bacteria, with these promoting nutrient attenuation. We therefore tested microbial metabolic activity, microbial composition, and their metabolic potential using Biolog-GN2 microplate culture and high-throughput sequencing of prokaryotic 16S rRNA gene amplicons. Our results showed that the FAWTS displayed high removal efficiencies for chemical oxygen demand (COD, 74.4-91.2 %), total nitrogen (TN, 66.9-86.8 %), and total phosphorus (TP, 76.2-95.9 %). Simultaneously, microbial metabolic activity for various carbon sources was significantly enhanced in FAWTS biofilms. Denitrifying and phosphorus-removing bacteria, such as Rhodobacter, were enriched in these biofilms, and genes participating in denitrification and the pathway from methylphosphonate to α-D-ribose-1,5-bisphosphate were increased in the biofilm communities. These results imply that the transformed multi-step purification system effectively removed N, P, and COD from aquaculture wastewater by enhancing the bacterial communities involved in these processes. This suggests that contamination-free aquaculture is a feasible goal, and that microbial communities are central to pollutant removal.